Peran Ayah dalam Meningkatkan Kesehatan pada Ibu Hamil - Dwi Ribkhi Azizah; Vinami Yulian (Jurnal Keperawatan Silampari, 2023)
This study aims to determine fathers' role in improving pregnant women's health. The method used is a traditional literature review summarizing the latest understanding of a topic. The database used to obtain research articles uses accredited sites, namely Elsevier, SINTA, Pubmed, and Google Scholar. The study results show the influence exerted by the father in his role in improving the health of pregnant women. Based on the results of the analysis of the five kinds of literature that have been obtained, it is known that the role of the father in improving the health of pregnant women is divided into three categories, namely the influence of the father's role in improving the health of pregnant women, supporting factors for the position of fathers in improving the health of pregnant women, and inhibiting factors for the father's role in improving maternal health. The health of pregnant women. In conclusion, it is hoped that the husband or father can apply for assistance and support the mother and fetus during pregnancy based on the exposure described in this literature review so that the husband or father can be more aware of giving consent to the mother during pregnancy. Keywords: Pregnancy, Pregnant Women's Health, Father's Role